Influência da quantidade de dentifrício e concentração de fluoreto na retenção intrabucal de fluoreto em crianças - Hall, Kevin Bruce [UNESP] (2015)
This aim of this study was to evaluate fluoride (F) concentrations in saliva of children after brushing with dentifrices containing different F concentrations (0, 550 and 1100 ppm F) in different amount (0.1, 0.3 and 0.5 g). Volunteers (n=24, 8-10 years old) were randomly assigned into 9 experimental groups, according to the possible combinations of F concentrations in the dentifrices and amount used, following a double-blind, crossover protocol. They were instructed to brush their teeth with a placebo dentifrice, 3 times/day, during one week (wash out period). On the 7th day, stimulated saliva was collected prior to toothbrushing (baseline) with the assigned combination of dentifrice type and amount. Following, saliva samples were collected at 5, 15, 30, 60 and 120 min after toothbrushing and the protocol was then repeated for 8 additional weeks, in order to follow the crossover protocol. Saliva samples were then centrifuged and the supernatants were frozen until F analysis, which was carried out using ion-selective (Orion 9409) and reference (Orion 9002) electrodes after buffering with TISAB III. The area under the curve (AUC) for salivary fluoride clearance was calculated using the individual points (trapezoidal rule). Data of salivary flow rate, salivary F concentrations at each collection point, as well as of AUC were submitted to two-way, repeated measures ANOVA, followed by the Student-Newman-Keuls test (p<0.05). A marked peak in salivary fluoride concentrations was seen 5 min after brushing, decreasing exponentially afterwards. A clear dose-response relationship was seen between fluoride concentration and amount of dentifrice used and the mean AUC of salivary F concentrations (p<0.001). Toothbrushing with 0.3 and 0.5 g of the low-fluoride toothpaste (550 ppm F) led to significantly higher AUC values when compared with the...